Translation Techniques Used In Translating Proverbs Related To “NEBU-NEBU” From Karonese Language Into English - Tiara Pebina; Milisi Sembiring; Nurlaidy Simamora (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study is aimed to find out the translation techniques used in Translating Proverbs Related to “Nebu-Nebu” from Karonese Language into English Molina and Albir’s translation techniques are applied to translate the proverbs from the source language (SL) into the target language (TL). This study is conducted by Creswell’s descriptive qualitative method. The data is taken from a book entitled Peribahasa (Kuan-KuanenKaro) which is written by Pdt. Sada Kata Ginting Suka and Pdt. Dr. Elieser Perpulungen Ginting. The finding of this study shows that in translating the proverbs, there were literal translation, modulation, amplification, linguistic amplification, description, discursive creation, established equivalent, generalization, and adaptation translation techniques are used in translating the proverbs from Karonese language into English in this study.